Pendampingan Pendirian Dan Pelaksanaan Program Tahfidzul Qur’an Di Pondok Pesantren Al-Alif, Desa Tamanrejo - Solikin (Jurnal Studi Islam dan Sosial, 2020)
This study aims to see the empowerment process in establishing and implementing the Tahfidzul Qur'an Program at Al-Alif Islamic Boarding School, Tamanrejo Village. This empowerment process uses the Posdaya approach. Based on the results of the implementation of mentoring in the establishment and implementation of the Tahfidzul Qur'an Program at Al-Alif Islamic Boarding School, there are several conclusions as follows: 1) Assistance in the establishment and implementation of the Tahfidzul Qur'an Program is guided by the stages in the empowerment strategy based on posdaya; 2) The Tahfidzul Qur'an program has been implemented systematically and optimally; 3) All students began to memorize some of the letters in the Qur'an; 4) The students are very motivated to memorize the Qur'an. Santri are very enthusiastic in memorizing the Qur'an. This situation is evidenced by several factors, among others, they enjoy memorizing the Qur'an, memorizing the Qur'an is done by reading it repeatedly or reading it together, and when reading the verses of the Qur'an, they read well and sequentially or systematically; and 5) The establishment of the Tahfidzul Qur'an Program has positive implications in participating in protecting the Qur'an. One form of appreciation for the Qur'an is that the Qur'an from generation to generation is always memorized and maintained in the chest of the memorizers (huffazh) of the Qur'an.